Late Miocene magnetostratigraphy of Jianzha Basin in the northeastern margin of the Tibetan Plateau and changes in the East Asian summer monsoon. (8th November 2017) - Fu, Chaofeng; Qiang, Xiaoke; Xu, Xinwen; Xi, Jianjian; Zuo, Jun; An, Zhisheng
Abstract : Jianzha Basin is located in the northeastern Tibetan Plateau (NETP) and contains a thick sequence of Cenozoic sediments that are an archive of information about the growth of the Tibetan Plateau and the evolution of the arid environment of the interior of Asia. Here, we present magnetostratigraphic and palaeoenvironmental records from a 361‐m‐thick sequence of Late Cenozoic eolian Red Clay and intercalated fluviolacustrine deposits in the Jianzha Basin. The magnetostratigraphic results show that the sediments have recorded a continuous geomagnetic polarity sequence from C5r.3r to C3r, spanning the interval from 11.8 to 5.8 Ma in the Late Miocene. There are two intervals of rapidly fluctuating sedimentation rates between ~10 and ~6 Ma, which we interpret as a response to a series of uplifts and expansions to the north and to the east in the NETP. The fluctuations in Rb/Sr ratio and magnetic susceptibility before ~8.57 Ma reflect intensified East Asian summer monsoon (EASM) precipitation which resulted from the growth of the NETP. From ~8.57 to ~7.21 Ma, the EASM was impacted by global cooling and ice build‐up in the Northern Hemisphere in addition to the uplift of the Tibetan Plateau (TP) in the Late Miocene. From ~8.57 to ~7.21 Ma, there is a lack of coherency between the fluctuations in MS and Rb/Sr ratio; however, subsequently, there is significant coherency between the Rb/Sr ratio and the deep‐sea oxygen isotope record present. This suggests that from ~8.57 Ma, the eolian Red Clay sediments in the Jianzha Basin were significantly affected by the addition of dust derived from the deforming and uplifting areas of the TP.